Stationary in Distributions of Numerical Solutions for Stochastic Partial Differential Equations with Markovian Switching - Yi Shen; Yan Li (Abstract and Applied Analysis)
We investigate a class of stochastic partial differential equations with Markovian switching. By using the Euler-Maruyama scheme both in time and in space of mild solutions, we derive sufficient conditions for the existence and uniqueness of the stationary distributions of numerical solutions. Finally, one example is given to illustrate the theory.